Experimental blunt chest trauma – cardiorespiratory effects of different mechanical ventilation strategies with high positive end-expiratory pressure: a randomized controlled study. Issue 1 (December 2015) - Schreiter, Dierk; Carvalho, Nadja; Katscher, Sebastian; Mende, Ludger; Reske, Alexander; Spieth, Peter; Carvalho, Alysson; Beda, Alessandro; Lachmann, Burkhard; Amato, Marcelo; Wrigge, Hermann; Reske, Andreas
Abstract Background Uncertainty persists regarding the optimal ventilatory strategy in trauma patients developing acute respiratory distress syndrome (ARDS). This work aims to assess the effects of two mechanical ventilation strategies with high positive end-expiratory pressure (PEEP) in experimental ARDS following blunt chest trauma. Methods Twenty-six juvenile pigs were anesthetized, tracheotomized and mechanically ventilated. A contusion was applied to the right chest using a bolt-shot device. Ninety minutes after contusion, animals were randomized to two different ventilation modes, applied for 24 h: Twelve pigs received conventional pressure-controlled ventilation with moderately low tidal volumes (VT, 8 ml/kg) and empirically chosen high external PEEP (16cmH2 O) and are referred to as the HP-CMV-group. The other group (n  = 14) underwent high-frequency inverse-ratio pressure-controlled ventilation (HFPPV) involving respiratory rate of 65breaths · min−1, inspiratory-to-expiratory-ratio 2:1, development of intrinsic PEEP and recruitment maneuvers, compatible with the rationale of the Open Lung Concept. Hemodynamics, gas exchange and respiratory mechanics were monitored during 24 h. Computed tomography and histology were analyzed in subgroups. Results Comparing changes which occurred from randomization (90 min after chest trauma) over the 24-h treatment period, groups differed statistically significantly (all P values for group effect <0.001, General Linear Model analysis) for the following parameters (values are mean ± SD for randomization vs. 24-h): PaO2 (100 % O2 ) (HFPPV 186 ± 82 vs. 450 ± 59 mmHg; HP-CMV 249 ± 73 vs. 243 ± 81 mmHg), venous admixture (HFPPV 34 ± 9.8 vs. 11.2 ± 3.7 %; HP-CMV 33.9 ± 10.5 vs. 21.8 ± 7.2 %), PaCO2 (HFPPV 46.9 ± 6.8 vs. 33.1 ± 2.4 mmHg; HP-CMV 46.3 ± 11.9 vs. 59.7 ± 18.3 mmHg) and normally aerated lung mass (HFPPV 42.8 ± 11.8 vs. 74.6 ± 10.0 %; HP-CMV 40.7 ± 8.6 vs. 53.4 ± 11.6 %). Improvements occurring after recruitment in the HFPPV-group persisted throughout the study. Peak airway pressure and VT did not differ significantly. HFPPV animals had lower atelectasis and inflammation scores in gravity-dependent lung areas. Conclusions In this model of ARDS following unilateral blunt chest trauma, HFPPV ventilation improved respiratory function and fulfilled relevant ventilation endpoints for trauma patients, i.e. restoration of oxygenation and lung aeration while avoiding hypercapnia and respiratory acidosis.